Medicalized Masculinities: Tales of (In)Fertility, Sperm Donation, and Fatherhood (Altre Modernità, 2020)
Employing an intersectional approach—drawing on cultural and new kinship studies, (medical) anthropology, gender and media studies—this article analyzes how the 2013 MTV series Generation Cryo as cultural text deals with medicalized masculinities and (in)fertilities. It asks in what ways masculinities and also fathers, fathering, and fatherhoods are (re)presented and negotiated in a story which has sperm donation by an anonymous donor and the donor siblings and/in their respective families at its center. In the show, essentially an (auto)biographical narrative, all families emphasize social parenthood over genetic inheritance, yet there are also deep-seated insecurities (re)triggered by the donor who is literally and metaphorically a present absence transforming into a potential family member, thus shaking family tectonics and challenging familial/familiar gender and family roles. Generation Cryo is a story about donor conceived children, but also about clinically infertile men and their social roles as fathers, their struggles to narrate and embody individual forms of masculinities in the face of cultural normative templates of hegemonic masculinities— complex practices constantly oscillating between genetic essentialism and social parenthood.